2006
DOI: 10.1002/cne.20956
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalinergic afferents of the centromedial amygdala in the rat

Abstract: The connectivity of the amygdaloid complex has been extensively explored with both anterograde and retrograde tracers. Even though the afferents of the centromedial amygdala [comprising the central (CEA) and medial (MEA) amygdaloid nuclei] are well established, relatively little is known about the neuropeptide phenotype of these connections. In this study, we first examined the distribution of mu-opioid receptor (MOR) and delta-opioid receptor (DOR) in the amygdala via in situ hybridization and immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
112
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(116 citation statements)
references
References 91 publications
3
112
0
1
Order By: Relevance
“…The amygdala has a high density of GABA A and benzodiazepine receptor sites as well as opioid receptor sites (Shiosaka et al 1983;Mansour et al 1995a;Veinante et al 1997;Wilson et al 2002;Poulin et al 2006). The anxiolytic actions of benzodiazepines are thought to be mediated by neurons expressing the GABA A receptor containing the α2 subunit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The amygdala has a high density of GABA A and benzodiazepine receptor sites as well as opioid receptor sites (Shiosaka et al 1983;Mansour et al 1995a;Veinante et al 1997;Wilson et al 2002;Poulin et al 2006). The anxiolytic actions of benzodiazepines are thought to be mediated by neurons expressing the GABA A receptor containing the α2 subunit.…”
Section: Discussionmentioning
confidence: 99%
“…This particular subunit is largely localized in limbic structures, including the amygdala (Low et al 2000;Rudolph et al 2001). PreproENK mRNA is seen in various nuclei of the amygdala including the central, basolateral and posteroventral portion of the medial nucleus, and most of the ENK afferents to the centromedial amygdala arise from intra-amygdaloid sources or the bed nucleus of the stria terminalis (BNST) (Poulin et al 2006). Combined with our previous data (Kang et al 2000) and the localization of reporter (GFP) expression (Figure 1b), this suggests that viral overexpression most likely changes intraamygdalar ENK projections that subsequently modulate diazepam effects in the plus maze.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using consumption and taste-reactivity measures of palatability in rodents, several groups have reported evidence of an opioid receptor-mediated network within the circuitry of the nucleus accumbens shell and ventral pallidum mediating hedonic processing or reward ''liking'' based on the palatability-enhancing effects of locally infused opioid agonists (5)(6)(7)(8). However, although opioid processes often have been proposed to convey the affective properties of natural rewards (9,10), opioid peptide-containing neurons and receptors are present in multiple basal forebrain regions (11,12) implicated not in reward hedonia but rather in the learning process that mediates goal-directed actions. In particular, several studies have found the opioid receptor-rich basolateral amygdala (13) to be important for encoding the incentive value of the rewards that support the performance of goal-directed actions in rats (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Anatomically, the amygdala is subdivided into central, medial, cortical, basomedial and basolateral nuclei. Among these nuclei, the central nucleus has abundant proenkepha-lin, proopiomelanocortin (POMC) and prodynorphin nerve fibers (Finley et al 1981;Khachaturian et al 1982;Fallon and Leslie 1986;Cassell and Gray 1989;Cassell et al 1999;Poulin et al 2006). The opioid nervous system in the central amygdala associates with pain, fear, anxiety, stress and feeding behavior (Davis et al 1994;Bernard et al 1996;Pitkanen et al 1997;LeDoux 2000;Swanson 2000;Petrovich and Gallagher 2003).…”
Section: Introductionmentioning
confidence: 99%